A Separate Calibration Method of Laser Pointing and Ranging for the GF-7 Satellite Laser That Does Not Require Field Detectors - Ren Liu; Junfeng Xie; Chaopeng Xu; Junze Zeng; Fan Mo; Xiaomeng Yang (Remote Sensing, 2022)
Satellite laser altimeters have been widely used in the surveying, mapping, forestry, and polar regions and by other industries due to their excellent elevation measurement accuracy. Satellite laser on-orbit geometry calibration is a necessary means to ensure elevation accuracy. This study proposes an iterative geometry calibration method for satellite laser altimeter pointing and ranging separation that does not require the use of field detectors. The DSM data were first used to complete the laser pointing calibration, and then the laser footprint elevation was measured accurately to complete the laser ranging calibration. The iterative calibration experiment was repeated until the convergence condition (i.e., the laser point difference was less than 1 × 10-5 degrees and the laser ranging difference was less than 0.01 m) was met, with the calibrated laser pointing angle and ranging separation used as the input parameters. In this work, the GaoFen-7 (GF-7) satellite laser was used as the test object and the actual laser pointing and ranging values derived from ground detector calibrations. The results verified that the pointing accuracy of the GF-7 beam 1 was 2 arcsec and that the ranging accuracy was 2 cm after applying the calibration method presented in this paper. The pointing accuracy of the GF-7 beam 2 was 2.2 arcsec, and the ranging accuracy was approximately 1 cm. This analysis demonstrated that the GF-7 laser mission exceeded its pointing angle requirement of 3 arcsec after laser pointing and ranging separation iterative calibrations were applied. Finally, ground control points were used to verify the calibrated elevation accuracy of the GF-7 satellite laser, and its accuracy on flat terrain was 0.18 m. In summary, it was proven that the satellite laser geometry calibration method proposed in the article is effective.